Atypical moral judgment following traumatic brain injury - Martins, Ana Teresa (2012)
Previous research has shown an association between emotions, particularly social emotions, and moral judgments. Some studies suggested an association between blunted emotion and the utilitarian moral judgments observed in patients with prefrontal lesions. In order to investigate how prefrontal brain damage affects moral judgment, we asked a sample of 29 TBI patients (12 females and 17 males) and 41 healthy participants (16 females and 25 males) to judge 22 hypothetical dilemmas split into three different categories (non-moral, impersonal and personal moral). The TBI group presented a higher proportion of affirmative (utilitarian) responses for personal moral dilemmas when compared to controls, suggesting an atypical pattern of utilitarian judgements. We also found a negative association between the performance on recognition of social emotions and the proportion of affirmative responses on personal moral dilemmas. These results suggested that the preference for utilitarian responses in this type of dilemmas is accompanied by difficulties in social emotion recognition. Overall, our findings suggest that deontological moral judgments are associated with normal social emotion processing and that frontal lobe plays an important role in both emotion and moral judgment.